Renewed Explosive Phreatomagmatic Activity at Poás Volcano, Costa Rica in April 2017 - Salvage, Rebecca O.; Avard, Geoffroy; de Moor, J. Maarten; Pacheco, Javier F.; Brenes Marin, Jorge; Cascante, Monserrat; Muller, Cyril; Martinez Cruz, María (Frontiers in Earth Science, 2018)
Phreatic and phreatomagmatic eruptions at volcanoes often present no short term precursory activity, making them a challenge to forecast. Poás volcano, Costa Rica, exhibits cyclic activity with phreatic and some phreatomagmatic eruptions separated by times of quiescence. The latest phreatomagmatic stage began in March 2017 with increases in crater lake temperatures, SO2 flux, and the rate of seismicity, as well as accelerated ground inflation near the active crater. On 23 April 2017 at 04:12 UTC, a large phreatomagmatic eruption occurred at Poás, sending blocks up to 1 m in length to distances >1 km. Hindsight analysis revealed a precursory seismic sequence from 25 March to 22 April of similar seismic events (in terms of their frequency and waveform characteristics). Fourteen families of similar seismic events (containing ≥10 events per family) were identified during this precursory sequence, totaling over 1,300 events. An acceleration within the dominant family of LF (low frequency) waveforms was identified, suggesting that a forecast for the onset of the eruption may have been possible using the Failure Forecast Method (FFM). However, no confidence could be placed in the forecast generated, reiterating that not all accelerating trends are suitable for analysis using the FFM, in particular in conjunction with a least-squares linear regression. Our residual analysis further supports the concept that using a least-squares linear regression analysis is not appropriate with this dataset, and allows us to eliminate commonly used forecasting parameters for this scenario. However, the identification of different families of similar seismicity allows us to determine that magmatic fluid on its way to the surface initially became stalled beneath a chilled margin or hydrothermal seal, before catastrophically failing in a large phreatomagmatic eruption. Additionally, we note that 24 h prior to the large phreatomagmatic eruption, all LF families became inactive, which could have been falsely interpreted in real time as the waning of activity. Our results suggest that identifying families of seismicity offers unique opportunities to better understand ongoing processes at depth, and to challenge conventional forecasting techniques.